2020
DOI: 10.1172/jci.insight.134310
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of FAT and DCHS protocadherins during hypothalamic-pituitary development

Abstract: Pituitary developmental defects lead to partial or complete hormone deficiency and significant health problems. The majority of cases are sporadic and of unknown cause. We screened 28 patients with pituitary stalk interruption syndrome for mutations in the FAT/DCHS family of protocadherins that have high functional redundancy. We identified 7 variants, 4 of which are putatively damaging, in FAT2 and DCHS2 in 6 patients with pituitary developmental defects recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Aside from ciliogenesis, FUZ is also a Planar Cell Polarity (PCP) pathway effector, a pathway which we have previously examined in the pituitary in the context of receptor‐ligand FAT/DCHS protocadherins. Mutations in FAT/DCHS family result in pituitary phenotypes ranging from morphological defects of the anterior pituitary, interrupted pituitary stalk and ectopic posterior pituitary (Lodge et al, 2020 and see Voutetakis, 2021 for comprehensive review on pituitary stalk anomalies). However, these phenotypes do not overlap with what we see in Fuz −/− mutations, which appear consistent with defects in SHH signalling rather than PCP defects.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from ciliogenesis, FUZ is also a Planar Cell Polarity (PCP) pathway effector, a pathway which we have previously examined in the pituitary in the context of receptor‐ligand FAT/DCHS protocadherins. Mutations in FAT/DCHS family result in pituitary phenotypes ranging from morphological defects of the anterior pituitary, interrupted pituitary stalk and ectopic posterior pituitary (Lodge et al, 2020 and see Voutetakis, 2021 for comprehensive review on pituitary stalk anomalies). However, these phenotypes do not overlap with what we see in Fuz −/− mutations, which appear consistent with defects in SHH signalling rather than PCP defects.…”
Section: Discussionmentioning
confidence: 99%
“…Apical protein NF2 (Merlin) and AMOTs have also been linked to upstream regulation of LATS activity [ 56 ]. Additionally, in Drosophila and some mammalian tissues, the Hippo pathway can be regulated via the atypical protocadherins Fat and Dachsous [ 56 ], although within the pituitary, mutations in FAT4 and DCHS1/DCHS2 do not appear to influence YAP/TAZ function [ 57 ]. Extracellular control of the Hippo pathway within the pituitary remains to be elucidated.…”
Section: Signalling In the Postnatal Pituitary Stem Cell Nichementioning
confidence: 99%
“…Furthermore an association can occur between PSIS and extrapituitary abnormalities such as biliary ciliopathy with homozygous TTC26 mutations 123 and Fanconi anaemia 119,124,125 .However, like SOD, a polygenic and multifactorial aetiology is probable, and, in one study, up to 83% of patients with sporadic PSIS have multiple heterozygous variations in genes largely affecting Notch, Shh and Wnt signalling 124 . More recent whole-exome studies from 2018 and 2020 have identified further candidate genes (for example, FAT2, DCHS1, DCHS2, ROBO2, CCDC88C, KIF14and KAT6A) 126,127 .…”
Section: [H2] Multiple Pituitary Hormone Deficiencymentioning
confidence: 99%